Aplikasi Mikrokontroler Atmega8535 Pada Robot Cerdas Pengangkut Tempat Sampah (Box) Menggunakan Sensor Warna Tcs3200 - Suhada Suhada; Hasdari Helmi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
The robot is a tool that is basically serves to make something easy in human’s work. Trash hauler robot can be utilized by people to assist in providing ease for the cleanlines of the environment. The robot uses program language C which is processed in application of CodeVision AVR. Completion of the steps in the application of this research is to design a program, create a program, do a test of the robot, refinement of program, and the last is the process of program improvement. The Program could be implemented by requiring there is hardware that will be output of the whole research result. The Program is inside of Microcontroller Application ATMega8535 on this intellegent robot of hauler (Box) Trash can be used as a guide for users of technology to increase knowledge  and continue the innovation of the useful new technology creation.